Frequency and Pattern of Peripheral Nerve Involvement in Firearm Injuries: A 10-year Neurophysiology Lab Experience - Sajjad, Ali; Saleem, Shafaq; Kanwar , Dureshahwar (Nepal Journal of Medical Sciences, 2025)
Introduction: To determine the frequency, pattern, and severity of peripheral nerve involvement in firearm-related injuries based on electrophysiological studies. To explore the frequency of surgical interventions performed after firearm-related nerve injuries. Methods: This was a retrospective cross-sectional study conducted in the neurophysiology department at the Aga Khan University Hospital (AKUH), Karachi, Pakistan. The study included all the patients with gunshot injuries and underwent two Electromyography and Nerve conduction studies (EMG/NCS) at least 8 weeks apart for follow-up. The data was analyzed by SPSS version 22.0. Results: Out of a total of 216 patients, firearm injury was seen most frequently in the lower limb 56.5% (n=122) mainly the Sciatic nerve 26.6% (n=54) followed by upper limb 35.6% (n=77) mainly brachial plexus 19.2% (n=39). Axonal-type nerve injury without evidence of reinnervation (i.e. severe) was the most frequent electrophysiological finding 79.8% (n=162). Conclusions: Firearm injury in limbs is associated with significant morbidity. The study describes various patterns and severity of firearm-related peripheral nerve injuries. Electrophysiological studies aid in localizing and assessing the severity of post-traumatic nerve injury further guiding the prognosis and candidacy of surgical intervention.